Student family through the eyes of Tuvan youth - Rostovskaya, Tamara K.; Zolotareva, Olga A.; Vasilieva, Ekaterina N.; Nakisbaev, Dmitriy V. (The New Research of Tuva, 2024)
The article presents the results of a nationwide sociological study “Student Families of Russia”, conducted in the Republic of Tuva in 2022. The study focuses on the marital and reproductive attitudes of students aged 18–25 in Tuva, specifically those attending Tuvan State University. The aim of the study was to assess the readiness of these young people to form families while studying.The findings of the study indicate that marriage registration does not appear to be the primary motivation for students in Tuva when it comes to establishing a family. Instead, postponement of childbirth until a later age is linked to their unstable economic situation. This highlights the importance of addressing issues such as family, education, and employment to increase the birth rate among young people. It is important for young families to achieve economic independence, and universities can help them do so by providing opportunities to combine education and work. We have formulated priority additional measures that will have a positive impact on student youth's decisions about starting a family and having children.These measures include supporting registered marriages and helping students with childcare. This will encourage more young people to start families and have children, which will help to increase the birth rate in Tuva.
Keywords: Tuvans; Tuva; Tuvan State University; student family; family model; registered marriage; birth rate